Effect of glyceryl trinitrate on the sphincter of Oddi motility and baseline pressure. Issue 2 (February 1985) - Staritz, M; Poralla, T; Ewe, K; Meyer zum Büschenfelde, K H
Abstract : It is widely accepted that glyceryl trinitrate (GTN) effectively dilates the smooth muscles of blood vessels. A similar effect has been postulated on the smooth muscles in the gastrointestinal tract. In this study the motility of the sphincter of Oddi and the common bile duct pressure as determined by endoscopic manometry was investigated in nine patients before and after sublingual application of 1.2 mg GTN (nitro group). Eight untreated patients served as controls. Three minutes after application of GTN the papillary contraction amplitude decreased from 69.3 +/- 4.3 mmHg to 36.8 +/- 5.1 mmHg (p less than 0.005) and the papillary baseline pressure fell from 8.9 +/- 0.6 mmHg to 2.9 +/- 0.2 mmHg (p less than 0.005) respectively. The contraction frequency in the nitro group and all motility parameters in the control group remained unchanged. These results indicate that GTN does not influence the sphincter of Oddi motility, but it relaxes very effectively the sphincter of Oddi muscle. Thus, GTN should be taken into account for the treatment of biliary colic. In our endoscopic unit GTN proved to be useful as premedication for endoscopic examinations, particularly for the removal of small and medium size common bile duct stones through the intact papilla.